Resistance of Animal Strains of Pseudomonas aeruginosa to Carbapenems - Haenni, Marisa; Bour, Maxime; Châtre, Pierre; Madec, Jean-Yves; Plésiat, Patrick; Jeannot, Katy (Frontiers in Microbiology, 2017)
Carbapenems are major antibiotics reserved to human medicine. This study aimed to investigate the mechanisms of carbapenem resistance of a selection of Pseudomonas aeruginosa veterinary strains from the French network resapath. Thirty (5.7%) imipenem and/or meropenem non-susceptible P. aeruginosa of canine (n=24), feline (n=5), or bovine (n=1) origin were identified in a large collection of 527 veterinary strains gathered by the French network Resapath. These resistant isolates belonged to 25 MultiLocus Sequence Types (MLST), of which 17 (68%) are shared with clinical (human) strains, such as high risk clones ST233 and ST395. Interestingly, none of the veterinary strains produced a carbapenemase, and only six of them (20%) harbored deletions or insertion sequence (IS) disrupting the porin OprD gene. The remaining 24 strains contained mutations or IS in various loci resulting in down-regulation of gene oprD coupled with upregulation of efflux system CzcCBA (n=3; activation of sensor kinase CzcS ± CopS), MexEF-OprN (n=4; alteration of oxido reductase MexS), MexXY (n=8; activation of two-component system ParRS), or MexAB-OprM (n=12; alteration of regulator MexR, NalC ± NalD). Two efflux pumps were co-produced simultaneously in three mutants. Finally, in 11 out of 12 strains displaying an intact porin OprD, derepression of MexAB-OprM accounted for a decreased susceptibility to meropenem relative to imipenem. Though not treated by carbapenems, animals thus represent a reservoir of multidrug resistant P. aeruginosa strains potentially able to contaminate fragile outpatients.